Reference Genome Anchoring of High-Density Markers for Association Mapping and Genomic Prediction in European Winter Wheat - Ladejobi, Olufunmilayo; Mackay, Ian J.; Poland, Jesse; Praud, Sebastien; Hibberd, Julian M.; Bentley, Alison R. (Frontiers in Plant Science, 2019)
In this study, we anchored genotyping-by-sequencing data to the International Wheat Genome Sequencing Consortium Reference Sequence v1.0 assembly to generate over 40,000 high quality single nucleotide polymorphism markers on a panel of 376 elite European winter wheat varieties released between 1946 and 2007. We compared association mapping and genomic prediction accuracy for a range of productivity traits with previous results based on lower density dominant DArT markers. The results demonstrate that the availability of RefSeq v1.0 supports higher precision trait mapping and provides the density of markers required to obtain accurate predictions of traits controlled by multiple small effect loci, including grain yield.